The Demand for Halal Certified Restaurants in Indonesia - Muniaty Aisyah; Leis Suzanawaty; Muhammad Said (International Journal of Supply Chain Management, 2019)
Rapid urbanizationthat lead to busier lifestyles with more time spent at work, and thus have less time for the preparation of meals at home, has heightened consumer demand for convenient restaurants. Since Indonesia has a large Muslim population, this research aims to find out the demand for halal certified restaurants by analyzing the influential factors involved in consumer intention and decision to patronize halalcertified restaurants based on the Theory of Planned Behavior. The method of analysis employed is Structural Equation Modeling,collected from 149 respondents in South Jakarta. This research elaborates on the findings which shows the relationship between attitude, subjective norm, perceived behavior control and consumer intention related to the decision to patronize halalcertified restaurants. It concludes by highlighting some summarized points for the restaurants' owner and manager to provide halal guarantee for Muslim consumers in Indonesia.